Building Sustainability Strategies in The Creative Culinary Industry Sector To Enhance Tourist Destination Attraction in Semarang Regency - Nurchayati; Riyadi, Bambang; Yunita, Lisa Efri (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Backgroud: The creative culinary industry plays a vital role in enhancing tourist destination attraction, serving as a cultural and culinary gateway for travelers. With growing awareness of sustainability and environmental concerns, it becomes imperative to investigate the development of sustainability strategies in this sector.Purpose: This study focuses on Semarang Regency, a burgeoning tourist destination, to assess the impact of sustainability strategies on attracting and retaining visitors.Design/methodology/approach: This quantitative research study was conducted with a sample of 250 respondents, comprising owners and managers of the culinary industry. The data were analyzed using Structural Equation Modeling (SEM) with WarpPLS 7.0 software.Finding/Result: The research unveiled significant relationships between sustainability strategies and tourist attraction. Environmental values were identified as a key driver, significantly influencing both cognitive and affective images. Additionally, low-carbon knowledge played a crucial role in shaping these images, highlighting the importance of eco-friendly practices and awareness in enhancing the industry's image. Cognitive and affective images were found to significantly contribute to the overall image of the sector, emphasizing their importance in shaping perceptions of sustainability efforts.Conclusion: These findings provide valuable insights for stakeholders in the creative culinary industry who are seeking to develop and implement sustainability strategies that enhance the attractiveness of tourist destinations in Semarang Regency.Original/value (State of the art): This study contributes to the understanding of how sustainability strategies can be effectively integrated into the creative culinary industry to boost tourist destination appeal. Keywords: business strategy, sustainability strategies, tourist destination, creative industry, Semarang